ANALISIS KRITIS HERMENEUTIK LINGUISTIK ARAB: KAJIAN HADIS KESETARAAN GENDER - Muhammad Khairul Fatihin; Lalu Rahmat Sugiara; Yogi Sopian Haris (Maulana Atsani: Jurnal Pendidikan Multidisipliner, 2025)
Traditional interpretations of several hadiths sometimes reflect the inequality embedded in religious practices and the understanding of Muslims. Specifically, this research aims to explore how the approach of Arabic linguistic hermeneutics can provide a more just, inclusive, and contextual understanding of these hadiths. This research uses the library research method with a qualitative approach and Arabic linguistic hermeneutics as the analytical framework. The main focus of this research lies in the in-depth analysis of the Arabic language structure in selected hadiths and the examination of the socio-historical context in which these hadiths were delivered. This method allows researchers to critically reinterpret the hadith texts to find alternative meanings that are more responsive to gender equality issues. The research results show that there are three hadiths that have often been used as the basis for gender inequality, but through the appropriate linguistic and hermeneutic approaches, these hadiths can be reinterpreted more fairly. Emphasis on grammatical meaning, analysis of key words in Arabic, and understanding the social context when the hadith was delivered allow for interpretations that support the principle of equality between men and women in Islam.